PENERAPAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MATERI LUAS PERMUKAAN SERTA VOLUME KUBUS DAN BALOK DI KELAS VIII-8 SMPN 3 BIREUEN SEMESTER GANJIL TAHUN PELAJARAN 2021/2022 - Herawati, Herawati (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
This research aims to find out: Can the application of the Numbered Heads Together (NHT) learning model improve mathematics learning outcomes in the surface area and volume of cubes and blocks in class VIII-8 at SMPN 3 Bireuen? The research method used is classroom action research (PTK) which consists of 2 cycles. The research subjects were 35 students in Class VIII-8 of SMP Negeri 3 Bireuen for the 2021/2022 academic year. Data analysis uses cooperative descriptive analysis techniques by comparing initial conditions with the results achieved in each cycle, and qualitative descriptive analysis of observation results by comparing the results of observations and reflections in cycle I and cycle II. The increase in learning outcomes is shown by the percentage of completeness of learning outcomes obtained in the first cycle of student learning outcomes. Of the 35 students who took the first cycle test, 27 students (77.14%) completed the test while 8 students (22.86%) did not complete it. . In cycle II, the results obtained were that of the 35 students who took the cycle II test, 33 (94.29%) students completed the test, while 2 (5.71%) students did not complete it.